2000
DOI: 10.1136/gut.47.1.79
|View full text |Cite
|
Sign up to set email alerts
|

Non-pathogenic bacteria elicit a differential cytokine response by intestinal epithelial cell/leucocyte co-cultures

Abstract: Lactobacillus johnsonii, an intestinal isolate, showed reduced potential to induce proinflammatory cytokines but increased transforming growth factor beta mR A in leucocyte sensitised CaCO-2 cells. TNF-was identified as one of the early mediators involved in cellular cross talk. In the presence of leucocytes, discriminative activation of CaCO-2 cells was observed between enteropathogenic E coli and non-pathogenic bacteria. Conclusion-The diVerential recognition of non-pathogenic bacteria by CaCO-2 cells requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
296
0
8

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 424 publications
(318 citation statements)
references
References 56 publications
14
296
0
8
Order By: Relevance
“…As found in former experiments (16,17), apical stimulation of Caco-2 cells by nonpathogenic bacteria leads to an enhanced production of cytokines in the basolateral compartment of the coculture model. In parallel with conditions in the intestine, bacteria and leukocytes are separated from leukocytes by a layer of IEC.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…As found in former experiments (16,17), apical stimulation of Caco-2 cells by nonpathogenic bacteria leads to an enhanced production of cytokines in the basolateral compartment of the coculture model. In parallel with conditions in the intestine, bacteria and leukocytes are separated from leukocytes by a layer of IEC.…”
Section: Discussionsupporting
confidence: 72%
“…For this purpose, we used a coculture model that was previously established in our department (16,17). In this model, a layer of differentiated IEC (Caco-2 cells) separated an apical compartment (luminal side) from a basolateral one (blood side).…”
Section: Conjugated Primary Bile Salts Reduce Permeability Of Endotoxmentioning
confidence: 99%
“…Several lines of evidence in vivo and in vitro indicate that probiotics engage and interact with host immune and other mucosal cells (12,32,33). In this study, consumption of L. salivarius UCC118 Rif was associated with a speci c secretary IgA anti-UCC118 Rif response as detected in saliva by a dilution-controlled, protein-standardised ow cytometric detection system.…”
Section: Discussionmentioning
confidence: 59%
“…Indeed, they found that Caco-2 cells alone are hyporesponsive to challenge with non-pathogenic E. coli and L. sakei. On the contrary, when cultured with leukocytes, Caco-2 cells produce TNF-α and IL-1β after treatment with L. sakei, but also the antiinflammatory transforming growth factor (TGF)-β after L. johnsonii treatment [26].…”
Section: Immunomodulationmentioning
confidence: 99%